Glacial fluctuations since the 'Medieval Warm Period' at Rothera Point (western Antarctic Peninsula). (January 2016) - Guglielmin, Mauro; Convey, Peter; Malfasi, Francesco; Cannone, Nicoletta
At a global scale, there is no evidence for synchronous multi-decadal warm ('Medieval Warm Period', MWP) or cold ('Little Ice Age', LIA) periods in the late Holocene. On the other hand, there is good correspondence globally in the timing of MWP or LIA and phases of glacier retreat and advance, respectively, with local exceptions mainly explained by the precipitation regime. Antarctica exhibits contrasting patterns, both regarding the existence of these two historical climatic periods and the glacial responses to climatic forcing. Here, we present evidence for glacial retreat corresponding to the MWP and a subsequent LIA advance at Rothera Point (67°34′S; 68°07′W) in Marguerite Bay, western Antarctic Peninsula. Deglaciation started at ca. 961–800 cal. yr BP or before, reaching a position similar to or even more withdrawn than the current state, with the subsequent period of glacial advance commencing between 671 and 558 cal. yr BP and continuing at least until 490–317 cal. yr BP. Based on new radiocarbon dates, during the MWP, the rate of glacier retreat was 1.6 m yr −1, which is comparable with recently observed rates (~0.6 m yr −1 between 1993 and 2011 and 1.4 m yr −1 between 2005 and 2011). Moreover, despite the recent air warming rate being higher, the glacial retreat rate during the MWP was similar to the present, suggesting that increased snow accumulation in recent decades may have counterbalanced the higher warming rate.